In-Person and Video-Based Post-Traumatic Stress Disorder Treatment for Veterans: A Location–Allocation Model. Issue 2 (1st February 2014) - Musdal, Hande; Shiner, Brian; Chen, TeChieh; Ceyhan, Mehmet E.; Watts, Bradley V.; Benneyan, James
ABSTRACT: Post-traumatic stress disorder (PTSD) is associated with poor health but there is a gap between need and receipt of care. It is useful to understand where to optimally locate in-person care and where video-based PTSD care would be most useful to minimize access to care barriers, care outside the Veterans Affairs system, and total costs. We developed a service location systems engineering model based on 2010 to 2020 projected care needs for veterans across New England to help determine where to best locate and use in-person and video-based care. This analysis determined specific locations and capacities of each type of PTSD care relative to patient home locations to help inform allocation of mental health resources. Not surprisingly Massachusetts, Connecticut, and Rhode Island are well suited for in-person care, whereas some rural areas of Maine, Vermont, and New Hampshire where in-patient services are infeasible could be better served by video-based care than external care, if the latter is even available. Results in New England alone suggest a potential $3, 655, 387 reduction in average annual total costs by shifting 9.73% of care to video-based treatment, with an average 12.6 miles travel distance for the remaining in-person care.